Proportion and patterns of ocular morbidity among garment workers in Savar, Dhaka, Bangladesh - Pathan, Farhan A.; Kabir, M. S.; Chowdhury, Nirupam; Fazrin, Sumaiya; Kawser, Fatiha (International Journal Of Community Medicine And Public Health, 2025)
Background: Ocular morbidity is a growing but neglected issue among garment workers in low- and middle-income countries, with poor lighting, dust, and near work raising risks. Despite their vital role in Bangladesh’s economy, research and interventions on their eye health remain scarce. Methods: A cross-sectional study was conducted among 250 garment workers (18-60 years) from two Savar factories (August 2023 to July 2024). Participants engaged in fine near work were randomly selected, while others were excluded. Data was collected via interviews and comprehensive ocular examinations. Ethical approval was gotten, and data were analyzed using statistical package for the social sciences (SPSS) version 26. Results: Among 250 garment workers examined, most were male (62%) and aged 21-30 years (47.2%; mean 30.98±8.39). Normal visual acuity was found in 78.8% (right eye) and 75.2% (left eye). Anterior segment diseases (61.2%) were more common than posterior (1.2%). Refractive errors were the leading morbidity (35.2%), mainly myopia (21.2%), followed by presbyopia (7.2%), blepharitis (2.4%), cataract (1.6%), and diabetic retinopathy (0.8%). Overall, 62.4% had at least one ocular morbidity. Conclusion: This study expresses a high burden of refractive errors and anterior segment diseases among Savar garment workers, highlighting the vital need for policy-driven eye screening and better workplace conditions.